Dietary restriction delays aging, but not neuronal dysfunction, in Drosophila models of Alzheimer's disease - Kerr, F; Augustin, H; Piper, M D W; Gandy, C; Allen, M J; Lovestone, S; Partridge, L (Neurobiology of Aging, 2009)
Dietary restriction (DR) extends lifespan in diverse organisms and, in animal and cellular models, can delay a range of aging-related diseases including Alzheimer's disease (AD). A better understanding of the mechanisms mediating these interactions, however, may reveal novel pathways involved in AD pathogenesis, and potential targets for disease-modifying treatments and biomarkers for disease progression. Drosophila models of AD have recently been developed and, due to their short lifespan and susceptibility to genetic manipulation, we have used the fly to investigate the molecular connections among diet, aging and AD pathology. DR extended lifespan in both Arctic mutant Aβ42 and WT 4R tau over-expressing flies, but the underlying molecular pathology was not altered and neuronal dysfunction was not prevented by dietary manipulation. Our data suggest that DR may alter aging through generalised mechanisms independent of the specific pathways underlying AD pathogenesis in the fly, and hence that lifespan-extending manipulations may have varying effects on aging and functional declines in aging-related diseases. Alternatively, our analysis of the specific effects of DR on neuronal toxicity downstream of Aβ and tau pathologies with negative results may simply confirm that the neuro-protective effects of DR are upstream of the initiating events involved in the pathogenesis of AD.